The nature and relevance of F.V. Foerster’s ethical-pedagogical ideas - Aramavičiiite, Vanda (Acta Paedagogica Vilnensia, 1993)
Bearing in mind that that the main task of the school is education of a versatile personality, more attention should be given to moral upbringing. For this purpose, of use could be ideas of F.V. Foerster, the famous teacher of morality, about significance of morality in the development of civilization and culture, as well as the role of moral education. Foerster considered moral upbringing to be a religious, social and psychological phenomenon. Discussing educational goals and objectives, opportunities and methods Foerster paid particular attention to the formation of character, cultivation of will, individual approach to the child, to taking into account gender specificities, as well as the trust in a child. This is especially true in the education of pedagogically neglected children and those with behavioural disorders. Educator’s role is not only to encourage and punish, but first of all to emphasize the positive, healthy inclinations of a child, figuratively speaking, an educator must inspire the child’s courage to pull himself out of the mud.